The Influence of Celebrity Effect on Commercial Brand Marketing - Taking Nike as An Example - Wang, Xuanzhi (Transactions on Economics, Business and Management Research, 2024)
Nowadays, consumers tend to rush for celebrity endorsement, today's more transparent information, celebrity endorsement has been a business opportunity for many companies to take advantage of, through which the brand's influence is rapidly expanding, casting a lot of successful win-win case between the enterprise and the star, a lot of brands will go through the star endorsement to enhance the influence and sales, the star can also be in the co-operation to obtain income as well as more business opportunities, but this is not necessarily a sure-fire business, which contains a lot of decision-making and a lot of data analysis as support to ensure a successful partnership. This paper analyses the role of the celebrity effect in branding by using literature analysis, and marketing model analysis. It addresses the issue of reliance on the celebrity effect and how brand loyalty can be sustained due to the fan effect. In response to these issues, brands can optimize their branding by strengthening community ties, linking online and offline, and combining multiple marketing tools with the celebrity effect.